Application Cosmic Lora Ray for the Development of Peatland Forest Fire Prevention System in Indonesia - Lianda, Jefri; Amri, Hikmatul; Aripriharta (International Journal of Intelligent Systems and Applications in Engineering, 2023)
Peat forest fires are commonly observed in Riau Province, Indonesia, especially in the dry season. These occurrences are often caused by the bad disposal of cigarette butts or the uncontrolled burning of specific garden areas. Hence, this study aims to develop an air-monitoring technology capable of transmitting data from several sensor nodes, to predict the state of normality in specific forest areas. The data of air temperature, humidity, and smoke density were obtained and transferred from the transmitting point (client) to the receiving (server) nodes. The server was a single system containing solar panels, a charging system, Li-Ion batteries, temperature and Smoke sensor, 20x4 server-side character LCD, and a Cosmic LoRa Ray-based microcontroller. The temperature and smoke sensors realistically recorded the air temperature and humidity, and the smoke density, respectively. The data of these two systems were also transferred to the microcontroller for processing before transmission to the server, and the results obtained were then displayed in a 20x4 character LCD.